1990
DOI: 10.1080/02783199009553290
|View full text |Cite
|
Sign up to set email alerts
|

The social and nonsocial behaviors of precocious preschoolers during free play

Abstract: From observing 26 precocious preschoolers during free play, it was determined that they engaged in high frequencies of associative and dramatic play. The girls engaged in more cooperative and less solitary play than the boys. The older children participated in more solitary, parallel, and less cooperative and less dramatic play than their younger peers. The higher IQ group (median IQ = 160+) undertook less constructive and more dramatic play than the lower IQ group (median IQ = 137).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
5

Year Published

1992
1992
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
(17 reference statements)
0
7
0
5
Order By: Relevance
“…peers (Hollingworth, 1931;Janos & Robinson, 1985;Monks & Ferguson, 1983;Olszewski-Kubilius, Kulieke, & Krasney, 1988;Purkey, 1966;Robinson & Noble, 1991;Silverman, 1993;Terman, 1925;Wright, 1990). In a comprehensive review of the literature, Robinson and Noble (1991) reported Perusal of a large group of studies of preadolescent children revealed [that] ... as a group, gifted children were seen as more trustworthy, honest, socially competent, assured and comfortable with self, courteous, cooperative, stable, and humorous, while they were also seen as showing diminished tendencies to boast, to engage in delinquent activity, to aggress or withdraw, to be domineering, and so on.…”
Section: K Silvermanmentioning
confidence: 99%
“…peers (Hollingworth, 1931;Janos & Robinson, 1985;Monks & Ferguson, 1983;Olszewski-Kubilius, Kulieke, & Krasney, 1988;Purkey, 1966;Robinson & Noble, 1991;Silverman, 1993;Terman, 1925;Wright, 1990). In a comprehensive review of the literature, Robinson and Noble (1991) reported Perusal of a large group of studies of preadolescent children revealed [that] ... as a group, gifted children were seen as more trustworthy, honest, socially competent, assured and comfortable with self, courteous, cooperative, stable, and humorous, while they were also seen as showing diminished tendencies to boast, to engage in delinquent activity, to aggress or withdraw, to be domineering, and so on.…”
Section: K Silvermanmentioning
confidence: 99%
“…In this area, several studies demonstrated that gifted children tend to be more popular and enjoy other children more than children who are not identified as gifted (Grace & Booth, 1958, Heber, 1956Terman, 1925;Wright, 1990).…”
mentioning
confidence: 97%
“…Provost & LaFreniere (1991) found that rates of active, focused solitary play in preschool were positively related to teachers' assessments of children's autonomy. Some studies have found that boys engage in solitary play more than girls (Provost & LaFreniere, 1991;Wright, 1990). While this is not a consistent statistic, it is interesting because our culture tends to encourage autonomy more in boys than in girls.…”
Section: Benefits Of Solitary Playmentioning
confidence: 86%